2021
DOI: 10.1177/0733464821996864
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Adaptations to the Call for Social Distancing and Use of Technology: Insights From Socioemotional Selectivity Theory and Lived Experiences

Abstract: Social distancing guidelines during COVID can be isolating, especially for older adults, with potential for poor health outcomes. Technology offers opportunities for remote connection, yet, older adults’ use of and perspectives on technology during this time remain largely unknown. The purpose of this study was to gain insight into older adults’ technology use and preferences to inform the development of a technology training intervention to support older adult well-being. Semi-structured interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Emotional stability in older adults is attributed to maintaining a balance through experience, coping strategies, and emotional control. SST research also supports that older adults maintain a greater sense of social and emotional well‐being even during times of crisis such as a pandemic (Bardach et al, 2021; Carstensen et al, 2020; Jiang, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 70%
See 2 more Smart Citations
“…Emotional stability in older adults is attributed to maintaining a balance through experience, coping strategies, and emotional control. SST research also supports that older adults maintain a greater sense of social and emotional well‐being even during times of crisis such as a pandemic (Bardach et al, 2021; Carstensen et al, 2020; Jiang, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 70%
“…The Socioemotional Selectivity Theory (SST) provides a framework for examining the association between age and socioemotional well‐being. The SST model was proposed by Carstensen (1987) and has been refined, researched, and validated in numerous studies (Abu‐Kamel & Alnazly, 2021; Bardach et al, 2021; Carstensen, 1992; Carstensen et al, 2020: Jiang, 2020; Patrick et al, 2021). The underlying premise of the theory postulates that social and emotional goals change based on the perception of time left to live (Carstensen, 2021; Carstensen & Hershfield, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, approximately 13 million older adults (38%) were not ready to use video visits with healthcare providers during the COVID-19 outbreak, largely due to a lack of confidence in and inexperience with technology that is required to communicate with healthcare providers ( Lam et al, 2020 ). Furthermore, older adults can face distinct challenges in learning and navigating a new technology, such as frustration in their interactions with new technology ( Bardach et al, 2021 ; Rogers & Fisk, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a general upward trend in online social engagement among older adults, disaster studies still report that older adults are concerned about the migration of disaster notifications toward tech-based messaging platforms and social media ( Bardach et al, 2021 ; Brockie & Miller, 2017 ; Gibson et al, 2020 ) that may leave them without access to critical and timely information. Nevertheless a qualitative study by Bardach et al (2021) found that most older adults were not interested in technology training, reporting that they had met a level of technology proficiency that met their needs.…”
Section: Introductionmentioning
confidence: 99%